2016
DOI: 10.18632/oncotarget.11784
|View full text |Cite
|
Sign up to set email alerts
|

β-escin selectively targets the glioblastoma-initiating cell population and reduces cell viability

Abstract: Glioblastoma multiforme (GBM) is a highly aggressive tumour of the central nervous system and is associated with an extremely poor prognosis. Within GBM exists a subpopulation of cells, glioblastoma-initiating cells (GIC), which possess the characteristics of progenitor cells, have the ability to initiate tumour growth and resist to current treatment strategies. We aimed at identifying novel specific inhibitors of GIC expansion through use of a large-scale chemical screen of approved small molecules. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…5 We too observed a drastic reduction in the stem-like properties in GSCs treated with the anti-gp130 blocking antibodies, assessed by both tumorsphere formation (Supplementary Figure S1a) and limiting dilution assays (Supplementary Figure S1b), as previously described. 7,8 However, and in contrast to the Shi et al work, no significant impact of anti-gp130 blocking antibodies was observed when GSCs were grown in complete media (Supplementary Figure S1a-b). Moreover, blocking gp130 had no overt impact on cell viability in any of the four GSCs tested (data for GSC4 and GSC9 not shown) in either EC-CM (Supplementary Figure S1c) or complete media (Supplementary Figure S1c).…”
mentioning
confidence: 58%
“…5 We too observed a drastic reduction in the stem-like properties in GSCs treated with the anti-gp130 blocking antibodies, assessed by both tumorsphere formation (Supplementary Figure S1a) and limiting dilution assays (Supplementary Figure S1b), as previously described. 7,8 However, and in contrast to the Shi et al work, no significant impact of anti-gp130 blocking antibodies was observed when GSCs were grown in complete media (Supplementary Figure S1a-b). Moreover, blocking gp130 had no overt impact on cell viability in any of the four GSCs tested (data for GSC4 and GSC9 not shown) in either EC-CM (Supplementary Figure S1c) or complete media (Supplementary Figure S1c).…”
mentioning
confidence: 58%
“…Animal Procedures. Tumor inoculation was performed on female Balb/C nude mice (Janvier) aged 6-7 weeks, as described previously 10 . Animals were randomly assigned to each group and group housed in specific pathogen free (SPF) conditions at 24ºC on a 12-hour daynight cycle.…”
Section: Antibodies and Reagents Cathepsinmentioning
confidence: 99%
“…GSCs constantly integrate external maintenance cues from their microenvironment, and as such represent the most adaptive and resilient proportion of cells within the tumor mass 5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…But blocking apoptosis could not reduce the β -escin-induced effect in sphere formation or stemness marker activity. This result suggests that β -escin directly changes the stem identity of GIC, independent of inducing the cell death [ 66 ]. Acori Graminei Rhizoma is used for traditional medicine, which has beneficial effects on CNS disorders.…”
Section: Apoptotic Effect Of Natural Productsmentioning
confidence: 99%